1994
DOI: 10.1139/f94-127
|View full text |Cite
|
Sign up to set email alerts
|

Aggregative Mating of Tanner Crabs,Chionoecetes bairdi

Abstract: In April 1991, a high-density mating aggregation of Tanner crabs, Chionoecetes bairdi, was discovered at 150 m depth near Kodiak, Alaska, with the research submersible DSRV Delta. The aggregation consisted primarily of oldshell, multiparous female crabs which formed mounds 1–2 m in diameter, 0.5–1.0 m high, and spaced at intervals of 1–2 m. Mounds contained hundreds of crabs each at densities > 100∙m−2. Male crabs were found mating with females at the periphery of the aggregation, with sex ratios (male to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 35 publications
1
18
0
2
Order By: Relevance
“…The observed burrowing behaviour in mud might serve to reduce predation, as suggested by Stevens et al (1994) for tanner crabs Chionoecetes bairdi. This burrowing behaviour was also observed for juvenile snow crabs in the field (Conan et al 1996) and for other species of crabs (Richards 1992, Zhou & Shirley 1998).…”
Section: Abiotic Factors Influencing Juvenile Distributionmentioning
confidence: 72%
“…The observed burrowing behaviour in mud might serve to reduce predation, as suggested by Stevens et al (1994) for tanner crabs Chionoecetes bairdi. This burrowing behaviour was also observed for juvenile snow crabs in the field (Conan et al 1996) and for other species of crabs (Richards 1992, Zhou & Shirley 1998).…”
Section: Abiotic Factors Influencing Juvenile Distributionmentioning
confidence: 72%
“…Because Tanner crabs have a behavior of burying in the sediment (Stevens et al 1994a) and red king crabs do not, a sand-mud habitat may be more important for Tanner crabs. Unlike the red king crab, the Tanner crab did not have a high density in the debris habitat.…”
Section: Discussionmentioning
confidence: 99%
“…Aggregation and podding behavior has been reported for both red king crabs and Tanner (Dew, 1990;Dew et al, 1992;Stevens et al, 1993Stevens et al, , 1994aStone et al, 1993). Stone et al referred to structurally dense and socially organized groups of adults as aggregations, and referred to them as pods when the majority of individuals were in physical contact with each other and stacked atop one another.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior has also been well documented for the Majidae, including Chionoecetes bairdi (Zhou & Shirley, 1997), Chionoecetes opilio (Comeau et al, 1998), Hyas lyratus (Stevens et al, 1992b), and Maja squinado (Sampedro & González-Gurriarán, 2004). Various reasons were proposed for the aggregation behaviour in the majids, including protection during moulting, location of mates, aid in food capture, and protection from predation (Powell & Nickerson, 1965;Stevens et al, 1994;Zhou & Shirley 1997;Gardner, 1999). Observations of M. squinado by Sampedro & González-Gurriarán (2004) suggested that this behaviour was based on protection from predation.…”
mentioning
confidence: 85%